KONTEKSTUALISASI KISAH MARYAM DI DALAM AL-QUR’AN SEBAGAI BASIS TELADAN GENERASI MUDA MUSLIM ERA KONTEMPORER - Tazkia Anugraheni Perdana (Taqaddumi: Journal of Quran and Hadith Studies, 2021)
One of the many stories that Allah tells in the Qur'an is the story of Maryam bint Imran, she was a tough woman and at the same time the mother of Prophet Isa. It has many features and lessons we can take from it. Knowledge of Islamic figures themselves is very minimal. Some people only think that these shop figures will only be discussed in religious studies and not practiced in everyday life. Unfortunately, if we practice what is contained in the al-Qur'an our life will be orderly and directed. The purpose of this research is to reintroduce the people of Maryam binti Imran who may have partly forgotten or even did not know anything about this. The method in this research is library research.